2013
DOI: 10.1556/avet.2012.049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of traditional and sensor-based electronic stethoscopes in beagle dogs

Abstract: The objective of this study was to compare the auscultatory findings using traditional and electronic sensor-based stethoscopes. Thirty-three adult healthy Beagles (20 females, 13 males, mean age: 4.8 years, range 1.4-8 years) were auscultated by four investigators with different experiences (INVEST-1, -2, -3 and -4) independently with both stethoscopes. Final cardiological diagnoses were established by echocardiography. Mitral murmurs were heard with both stethoscopes by all investigators and echocardiography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In our previous study aimed at comparing the diagnostic capacities of traditional and sensor-based electronic stethoscopes, we 'accidentally' detected 7 dogs with MVI (21%) among 33 clinically healthy Beagles (Szilvási et al, 2013). Based on our current results on 79 dogs, we demonstrated in an acceptably large Beagle population that MVI is a quite common disorder also in Beagles, as 20 (25.3%) dogs showed mild to moderate mitral valve regurgitation confirmed by Doppler echocardiography.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…In our previous study aimed at comparing the diagnostic capacities of traditional and sensor-based electronic stethoscopes, we 'accidentally' detected 7 dogs with MVI (21%) among 33 clinically healthy Beagles (Szilvási et al, 2013). Based on our current results on 79 dogs, we demonstrated in an acceptably large Beagle population that MVI is a quite common disorder also in Beagles, as 20 (25.3%) dogs showed mild to moderate mitral valve regurgitation confirmed by Doppler echocardiography.…”
Section: Discussionmentioning
confidence: 64%
“…In human patients, Berger et al (1989) concluded that a jet with a peak velocity of more than 4.0 m/sec may indicate abnormal mitral regurgitation. Table 2 Occurrence of mitral valve insufficiency (MVI) in clinically healthy dogs of various breeds Doppler echocardiography is considered to be the proper tool of diagnosing MVI and estimating its grade semi-quantitatively as has been done in this study and reported earlier (Pedersen et al, 1999a;Muzzi et al, 2003;Szilvási et al, 2013). Spectral Doppler echocardiography provides measurement values for maximal flow velocities of the regurgitant blood flow, but the semi-quantitative CFD technique alone is accepted for screening examinations (Olsen et al, 1999;Olsen et al, 2003;Trafny et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Various investigators have compared conventional stethoscopes (CS) and electronic stethoscopes (ES) for their ability to identify murmurs in people (Philip and Raemer, 1986;Grenier et al, 1998;Hoyte et al, 2005;Tavel, 2006) and dogs (V€ or€ os et al, 2012;Szilv asi et al, 2013). Furthermore, our group has also used both types of stethoscopes in a study on the occurrence of mitral valve insufficiency in healthy Beagle dogs (V€ or€ os et al, 2015).…”
Section: Introductionmentioning
confidence: 99%